Anisometropia Profile in Elderly Population: Tehran Geriatric Eye Study. Issue 3 (3rd July 2022) - Hashemi, Hassan; Jamali, Alireza; Nabovati, Payam; Yekta, Abbas Ali; Khabazkhoob, Mehdi
ABSTRACT: Purpose: To investigate the distribution and prevalence of anisometropia according to age, gender and ocular biometry in a geriatric population in Tehran, Iran. Methods: The present study was conducted on the geriatric population aged above 60 years. The study participants were selected using stratified random cluster sampling. The uncorrected and best-corrected visual acuity, dry objective (ARK510A, Nidek Co. 42 LTD, Aichi, Japan) and subjective refraction and ocular biometry (IOL Master 500; Carl Zeiss Meditec, Jena, Germany) were recorded for each patient. The magnitude and prevalence of anisometropia were evaluated in association with influential factors in cut-points of 0.50, 1.00, 1.50 and 2.00 diopter (D). Results: The mean age of participants (3237 individuals, 54% were female) was 68.19 ± 6.48 (range: 60–97) years. The mean anisometropia in the whole sample was 0.82 D (95% CI: 0.76 − 0.88 D), which increased from 0.62 D (in those aged 60–64 years old) to 1.36 D (in those above 80 years). The prevalence of anisometropia >1 D in total population, males, and females were 23.81%, 24.9%, and 22.76%, respectively. The odds ratio of anisometropia was higher in cases with cataracts, myopia compared to emmetropia, keratometry asymmetry, axial length asymmetry (P = .001), and corneal diameter asymmetry (all others, P < .001). Conclusion: The results of the present study show a high prevalence of anisometropia in elderly population, which was related to refractive error, cataract, age, gender, and ocular biometry asymmetry.